2023
DOI: 10.1021/acs.jafc.2c07539
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic and Transcriptome Analysis of the Inhibitory Effects of Bacillus subtilis Strain Z-14 against Fusarium oxysporum Causing Vascular Wilt Diseases in Cucumber

Abstract: Controlling cucumber Fusarium wilt caused by Fusarium oxysporum f. sp. cucumerinum (FOC) with Bacillus strains is a hot research topic. However, the molecular mechanism of Bacillus underlying the biocontrol of cucumber wilt is rarely reported. In this study, B. subtilis strain Z-14 showed significant antagonistic activity against FOC, and the control effect reached 88.46% via pot experiment. Microscopic observations showed that strain Z-14 induced the expansion and breakage of FOC hyphae. The cell wall thickne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
2
2
0
Order By: Relevance
“…33 Fu et al mentioned that arginine and proline metabolisms are closely related to the pathogenicity of fungi. 34 Similar to our results, Liu et al found that B. subtilis strain Z-14 and its antifungal lipopeptide conjugation were able to affect the energy synthesis and amino acid metabolism in F. oxysporum. 35 Aromatic amino acid metabolism, such as tyrosine, phenylalanine, and tryptophan, is usually associated with defense reactions such as the mangiferic acid pathway.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…33 Fu et al mentioned that arginine and proline metabolisms are closely related to the pathogenicity of fungi. 34 Similar to our results, Liu et al found that B. subtilis strain Z-14 and its antifungal lipopeptide conjugation were able to affect the energy synthesis and amino acid metabolism in F. oxysporum. 35 Aromatic amino acid metabolism, such as tyrosine, phenylalanine, and tryptophan, is usually associated with defense reactions such as the mangiferic acid pathway.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…subtilis strain Z-14 and its antifungal lipopeptide conjugation were able to affect the energy synthesis and amino acid metabolism in F. oxysporum . Aromatic amino acid metabolism, such as tyrosine, phenylalanine, and tryptophan, is usually associated with defense reactions such as the mangiferic acid pathway .…”
Section: Resultsmentioning
confidence: 99%
“…We also compared the fold change of qRT-PCR versus RNAseq for the DEGs verified by qPCR. RNA-seq data were highly correlated with qPCR data (y = 1.087x-0.1659, R 2 = 0.97), which confirmed the reliability of RNA-seq data 48 (Fig. 9(B)).…”
Section: Validation Of Rna-seq Data By Qrt-pcrsupporting
confidence: 69%
“…Plant Growth-Promoting Rhizobacteria (PGPR) are naturally occurring soil bacteria that can suppress plant diseases through antibiosis, induced systemic resistance, and competition with pathogens for nutrients and space (Lugtenberg and Kamilova 2009). Prior studies have demonstrated the potential effectiveness of PGPR applications against various major cucumber pathogens, including Fusarium oxysporum, Colletotrichum orbiculare, and Pseudoperonospora cubensis (Abo-Elyousr et al 2022;Ganphung et al 2022;Liu et al 2023). However, there is still limited research exploring the utilization of PGPR as a biocontrol agent specifically targeting C. cassiicola in cucumbers.…”
Section: Introductionmentioning
confidence: 99%